Implementation of Cause-Related Marketing Strategy in Increasing Consumer Engagement with Brands - R Dewi Pertiwi; Asri Sundari (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the implementation of Cause-Related Marketing (CRM) strategies in increasing consumer brand engagement. CRM is a form of corporate social responsibility that combines business objectives with social goals through partnerships between companies and non-profit organizations. This approach allows companies to focus not only on profits but also on contributing to social and environmental issues relevant to consumer values. This study used qualitative methods with a descriptive approach, through literature review, social campaign observations, and analysis of CRM implementation by several companies, such as Unilever (Lifebuoy and Molto) and Burger King. The results show that CRM strategies can strengthen emotional connections and consumer engagement with brands, enhance positive corporate image, and attract market segments such as Millennials and Gen Z, who care about social issues and sustainability. CRM also creates shared value between companies, social organizations, and communities through mutually beneficial partnerships. In conclusion, CRM has proven effective in building consumer brand engagement and loyalty. Authentic, consistent, and socially value-oriented CRM implementation can strengthen a company's reputation, foster consumer trust, and support sustainable development goals. Therefore, companies need to integrate social values into their marketing strategies to create long-term, profitable relationships between businesses, consumers, and communities.